Spectra of solar proton ground level events using neutron monitor and neutron moderated detector recordings - Stoker, P. H. (1985)
Recordings on relativistic solar flare protons observed at Sanae, Antarctic, show that the percentage increase in counting rates of the neutron moderated detector (4NMD) is larger than the percentage increase in counting rates of the 3NM64 neutron monitor. These relative increases are described by solar proton differential spectra j sub s(P) = AP(beta). The power beta is determined for each event and the hardnesses of the temporal variations of beta, found for the ground level events (GLE) of 7 May, 1978 and 22 November, 1977.